Efficacy and Safety of Adding 1 µg/Kg Dexmedetomidine to 20 ml Bupivacaine in Supraclavicular Brachial Plexus Block: A Randomized Trial - Ghoniem, Basma M.; Shams, Gamal Hendawy; Abdelsalam, Wafaa; Elsharkawy, Mahmoud Fawzy (Current Drug Safety, 2025)
BackgroundFor surgical procedures of the upper limbs, ultrasound-guided supraclavicular brachial plexus block (SCBPB) represents a safe substitute for general anesthesia. The present study evaluated the effectiveness and safety of incorporating 1µg/kg dexmedetomidine (DEX) into 20 ml bupivacaine, as opposed to using 20 ml and 30 ml bupivacaine without additives, in SCBPB.MethodsThis randomized, controlled, double-blind study included 75 patients assigned to elective upper-limb surgery under the mid-humerus level. Patients were randomized into three equal groups to receive US-guided SCBPB with 20 ml bupivacaine 0.5% + 1 μg/kg DEX in group BD, 20 ml bupivacaine 0.5% without additives in group B20, and 30 ml bupivacaine 0.5% in group B30 (control).ResultsCompared to group B20, groups BD and B30 had significantly quicker onset times for sensory and motor blocks. Groups BD and B30 had a more significant block duration than group B20. Group BD experienced considerably lower intraoperative hemodynamics than groups B20 and B30. Groups BD and B30 had a significantly delayed time to first rescue analgesia and consumed less pethidine than group B20. Compared to group B20, the pain score was significantly reduced in groups BD and B30. Comparable levels of pain score, rescue analgesia time, total pethidine consumption, and motor and sensory block onset and duration were seen in the BD and B30 groups.ConclusionDEX with a lower volume (20 ml) of bupivacaine reaches the same result as a higher volume of bupivacaine (30 ml) in managing perioperative pain and hemodynamic stability without the risk of the high volume of bupivacaine. Further, adding DEX to small dose of bupivacaine (20 ml) is more effective than small dose of bupivacaine (20 ml) alone without additives in prolonging the duration of sensory and motor block, reducing pain intensity, and delaying the need for rescue analgesia.
Keywords: dexmedetomidine